Study on large‐scale steam explosion of molten aluminum and water. Issue 4 (10th March 2020) - Shen, Zhengxiang; Chen, Hu; Lv, Zhongjie; Wang, Du; Chen, Dingyue; Huang, Fenglei
Abstract: Explosive interaction can be originated from an inadvertent contract of molten metal and water, and most explosive accidents to date have been reported in the aluminum industry. In most cases, this incident is not a major problem to production, but do occur at some plants. Most previous work at small‐scale experiments by bringing melt droplets into a water pool, with external trigger and controlled condition. These results are difficult to extend to large‐scale events for the effect of scale. A new self‐triggering test setup to deal with ~10 kg molten aluminum for interaction under open condition was designed in this article, and the explosion energetics were first measured quantitatively. Results show that the mild explosion often occurs at relatively high aluminum/water mass ratio. Conversely, an intense explosion is more likely with higher water content. The peak temperature of intense explosion is only 247°C, and the overpressure detected in the surroundings is about 0.113 MPa. It is suggested that the carbon steel with high surface wettability could promote a spontaneous explosion, and the merely addition of metal oxide has little effect on the initiation of explosion. In view of above, two possible explosion scenarios are assessed on the superheated limit theory.